PEMANFAATAN CITRA SENTINEL-2A UNTUK KERAPATAN VEGETASI DITINJAU DARI KEMIRINGAN LERENG DI PULAU BATAM - Ilfah Magdalina; Arif Roziqin (ABEC Indonesia, 2021)
Density of vegetation can be affected by the topography of the land in an area. Land surface in Batam Island is generally flat with hilly variation. The variation of land surface can be affected to density of vegetation. The method using Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI) and Soil Adjusted Vegetation Index (SAVI). Sentinel-2A imagery is used because this image has begun to various vegetation observation in remote sensing and has spatial resolution 10 m. The slope in Batam Island using DEMNAS data. The corelation of vegetation density with slope in Batam Island obtained from the correlation test and relationship. The result of correlation NDVI with slope is 0,39 included in low correlation (0,20-0,399). The result of correlation EVI and SAVI with slope is 0,44 and 0,45 included in moderate correlation (0,40-0,599).